Multiple X‐ray approaches to discriminate the origin of liquefied sand erupted during the 2012 Emilia Romagna earthquake. (19th June 2015) - Di Giuseppe, Dario; Tessari, Umberto; Faccini, Barbara; Coltorti, Massimo; Vaccaro, Carmela; Marin, Emanuela
: Geochemical, mineralogical and sedimentological analyses were carried out on sands erupted from sand volcanoes and soil cracks during the 2012 Emilia earthquakes with the aim of determining their origin and depth of provenance in a complex stratigraphic plain generated by different fluvial contributions. Geochemical, mineralogical and sedimentological analyses were performed by wavelength dispersive X‐ray fluorescence, X‐ray powder diffraction and Sedigraph and Settling tube, respectively. Distinct textural features, as well as Ni/MgO and Cr/Al2 O3 ratios, allow discriminating two populations: an A‐area located close to San Carlo village and a B‐area nearby Scortichino village. Sediments from A‐area show chemical and mineralogical characteristics well comparable with those of the sediments derived from the Apennine rivers, whereas sands from B‐area have strong similarities with the sediments from the Po river. In the earthquake crater area most of the liquefaction phenomena were related to superficial sandy deposits (fluvial ridges, paleochannels and crevasse splays) generated by Apennine rivers. The Po river sediments in the B‐area derive from a layer at a depth at which liquefaction phenomena were excluded, because of the greater lithostatic load. These sediments thus shed a new light on the mechanisms that may induce liquefaction during an earthquake or even without a seismic triggering. It is suggested that a gas phase (mainly methane), which is commonly found below the Po plain, could have been dissolved in the water, near to the saturation threshold or already exsolved, increasing the interstitial overpressure and facilitating the liquefaction and the eruption of the sandy sediments. Copyright © 2015 John Wiley & Sons, Ltd.